Green Accounting, Corporate Social Responsibility, Business Strategy, and Firm Value: Evidence from Indonesia - Santika, Sisca; Kusno, Hendra Sanjaya; Arazy, Dito Rozaqi; Ismail, Aida Hazlin (AKRUAL: JURNAL AKUNTANSI, 2025)
Introduction/Main Objectives: This paper investigates the influence of Green Accounting practices and Corporate Social Responsibility (CSR) disclosures on Firm Value in the Indonesian mining sector, highlighting the critical role of environmental and social responsibilities in corporate valuation. Background Problems: The research question centres on whether Green Accounting and CSR disclosures significantly affect Firm Value. The mining sector, known for its environmental and health risks, must adopt responsible practices to enhance Firm Value. Novelty: This study uniquely incorporates Business Strategy as a moderating variable in examining the relationship between Green Accounting, CSR disclosure, and Firm Value, filling a gap in existing literature on how business strategies impact these relationships. Research Methods: The research utilizes quantitative methods, analysing secondary data from annual and sustainability reports of mining companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The sample includes 25 companies selected based on criteria such as consistent reporting and profitability, with data processed using SmartPLS 3.2.9 software. Findings/Results: Results indicate that Green Accounting and CSR disclosures positively influence Firm Value. However, Business Strategy does not significantly moderate this relationship, suggesting that the direct effects of Green Accounting and CSR practices on Firm Value are substantial regardless of strategic variations. Conclusion: The study concludes that while Green Accounting and CSR disclosures are pivotal for enhancing Firm Value, Business Strategy does not notably modify this relationship. The implications highlight the necessity for companies to prioritize transparent environmental and social reporting to build stakeholder trust and improve Firm Value. The main takeaway is the essential role of sustainable practices in driving corporate performance and valuation, emphasizing the need for companies to integrate environmental and social responsibilities with financial performance.